Enhanced photocatalytic activity of nanostructured titanium dioxide/polyaniline hybrid photocatalysts. (14th December 2016) - Reddy, Kakarla Raghava; Karthik, K.V.; Prasad, S.B. Benaka; Soni, Sarvesh K.; Jeong, Han M.; Raghu, Anjanapura V.
Graphical Abstract: TiO2 /polyaniline hybrid photocatalysts were synthesized by chemical oxidative polymerization method showed superior photocatalytic performance than that of pristine TiO2 nanoparticles for the degradation of rhodamine, methylene blue and phenol organics. Abstract: An organo-inorganic photocatalytic nanocomposite material based on conjugated polymer, polyaniline (PANI) with titanium dioxide (TiO2 ) nanoparticles has been developed by performing in situ chemical oxidative polymerization of aniline with ammonium persulfate (APS) oxidant in the presence of hydrothermally synthesized TiO2 nanoparticles. The structural and morphological properties of TiO2 /PANI nanocomposites were analyzed by transmission electron microscopy (TEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR), respectively. The TEM results of the TiO2 /PANI nanocomposites showed that TiO2 nanoparticles of 5–10 nm of sizes are dispersed in the PANI matrix. FT-IR spectra show that the TiO2 /PANI nanocomposites are almost identical to the structure of PANI alone. The photocatalytic activities of the nanocomposites were evaluated by the photocatalytic degradation of Rhodamine B (RhB), Methylene Blue (MB) and phenol in the presence of UV-light irradiation. The composite catalysts exhibited higher photocatalytic activity for the degradation of organic pollutants than unmodified TiO2 nanoparticles, which is due to sensitizing effect of PANI.